STUDY OF "EFFECTIVENESS" CATEGORY IN THE SYSTEM OF SOCIETY`S SOCIO-ECONOMIC DEVELOPMENT - В. І. Осипов (Ринкова економіка: сучасна теорія і практика управління)
The article deals with the problem of the study of "Efficiency" category, which is crucial in the formation of a system of sustainable economic growth mechanism. We compared the "efficiency" category and the "effectiveness" and proposed forms of their use in economic research. An evaluation of the different points of view on the "efficiency" category. The attention is drawn to the fact that in order to ensure the global competitiveness of the economy in Ukraine we need to achieve an effectiveness of management system.